A Comparative Study of Accuracy of Shock Capturing Schemes for Simulation of Shock/Acoustic Wave Interactions. Issue 3 (June 2014) - Khotyanovsky, Dmitry V.; Kudryavtsev, Alexey N.; Ovsyannikov, Andrey Yu.
We simulate transmission of a small-amplitude disturbance wave through a shock wave. Results of our numerical experiments performed with different high-order shock-capturing schemes show that the capability of a scheme to correctly predict the amplification of the disturbances crucially depends on the Riemann solver used in evaluation of numerical fluxes. Incorrectly high amplification rates are produced by the solvers resolving shock waves sharply, with no interior points in numerical profiles of steady shock waves. In particular, both the exact Riemann solver and the popular Roe flux difference splitting demonstrate such unphysical behavior. A possible explanation of such behavior is proposed. More dissipative solvers, such as the global Lax–Friedrichs splitting, produce transmission coefficients close to the predictions of linear theory.